2021
DOI: 10.1016/j.red.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Production network structure, service share, and aggregate volatility

Abstract: This paper studies differences in production structures across countries and their implications for crosscountry heterogeneity in GDP volatility. In particular, economies with more input-output connections-a denser network-are associated with less concentrated sales shares and lower volatility. The relationship between density and volatility is stronger in countries with a higher share of services in GDP (hereafter referred to as service share). To account for this evidence, I propose a generalized production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…We complement the previous analysis by investigating in this section whether the effect of economic complexity on poverty can translate through the economic growth volatility channel. This is because on the one hand, a recent literature has shown that economic complexity is associated with lower aggregate output volatility (e.g., Güneri and Yalta, 2020;Miranda-Pinto, 2021), lower firms' output volatility (e.g., Maggioni et al, 2016), and dampens economic growth cycles (e.g., Canh and Thanh, 2020). On the other hand, a large body of the literature has now well established that greater macroeconomic volatility (e.g., output volatility) due, inter alia, to external shocks (e.g., financial crises and economic crises such as severe commodity prices shocks) adversely affects poor people, and raises poverty in developing countries 6 .…”
Section: Further Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We complement the previous analysis by investigating in this section whether the effect of economic complexity on poverty can translate through the economic growth volatility channel. This is because on the one hand, a recent literature has shown that economic complexity is associated with lower aggregate output volatility (e.g., Güneri and Yalta, 2020;Miranda-Pinto, 2021), lower firms' output volatility (e.g., Maggioni et al, 2016), and dampens economic growth cycles (e.g., Canh and Thanh, 2020). On the other hand, a large body of the literature has now well established that greater macroeconomic volatility (e.g., output volatility) due, inter alia, to external shocks (e.g., financial crises and economic crises such as severe commodity prices shocks) adversely affects poor people, and raises poverty in developing countries 6 .…”
Section: Further Analysismentioning
confidence: 99%
“…human development (e.g., Le Caous and Huarng, 2020), reduce economic growth volatility (e.g., Güneri and Yalta, 2020;Maggioni et al, 2016;Miranda-Pinto, 2021), dampen economic growth cycles (e.g., Canh and Thanh, 2020) and increase labor share notably in the context of (e.g., Arif, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, complex goods, i.e., sophisticated goods are those that have a high knowledge content, i.e., those with a high human capital intensity, (e.g., Bustos et al, 2012;Hausmann and Hidalgo, 2009;Hausmann and Hidalgo, 2011;Hidalgo, 2009). Additionally, some studies (e.g., Güneri and Yalta, 2020;Maggioni et al, 2016;Miranda-Pinto, 2021) have obtained empirically that complex economies 12 experience lower economic growth fluctuations, or lower economic growth cycles (e.g., Canh and Thanh, 2020).…”
Section: Effect Of Human Capital On Economic Growth Volatilitymentioning
confidence: 99%
“…This paper, therefore, falls partially within the literature on equilibrium multi-sector models first developed by Long and Plosser (1983), and later Horvath (1998Horvath ( , 2000, and Dupor (1999). Since then, a large body of work including Gabaix (2011), Foerster et al (2011, Acemoglu et al (2012), di Giovanni et al (2014), Atalay (2017), Baqaee and Farhi (2017b), Miranda-Pinto (2019), and others have worked out important features of those models for generating aggregate fluctuations from idiosyncratic shocks. 3 In contrast to this literature, the focus herein centers on the implications of production linkages for secular dynamics and the determination of both sectoral and aggregate trend growth rates.…”
Section: Introductionmentioning
confidence: 97%